(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم اختبار طيف الانعكاسية للبلورتين CdTeوCd0.96Yb0.04Te في مجال الطاقة من 1 إلى6eV في درجة حرارة الغرفة. إن التغيرات الملاحظة في أشكال الأطياف، بسبب وجود الايتيربيوم Yb، تم مقارنتها مع البنية القطاعية المحسوبة للمركب الثنائي CdTe المتوافرة في المراجع. تبين أن البنية القطاعية للمركب الثنائي في بعض المناطق حساسة إلى وجود الأيونات Yb، وأن إدخال Yb إلى البنية القطاعية للمادة CdTe أدى إلى ظهور قمة جديدة بقربeV2. نوقشت أيضاً الانتقالات الذرية الداخلية، نتيجة إدخال الايتيربيوم كإشابة إلى البلورة CdTe، في المادة Cd0.96Yb0.04Te. The reflectivity spectra of CdTe and Cd0.96Yb0.04Te crystals have been investigated in the 1-6eV energy range at room temperature. The observed changes in the shapes of the spectra, caused by the presence of ytterbium Yb, have been compared with the calculated band structure of binary compound CdTe available in the literature. The band structure in some regions seems to be sensitive to the presence of Yb ions. The introduction of Yb to band structure of CdTe material leads to the appearance a new maximum near 2eV. The intra-atomic transitions, due to ytterbium introduced as an impurity to the CdTe crystal, in the Cd0.96Yb0.04Te material were also discussed